Studies on the regulation of nitrogen metabolism in clostridium acetobutylicum NCP 262 and clostridium beijerinckii NCIMB 8052 - Quixley, Keith Windsor McRostie (Department of Molecular and Cell Biology, 2024)
In order to produce Clostridium acetobutylicum strains with improved solventogenic capabilities through genetic manipulation, a thorough understanding of the mechanisms governing solvent production is required. Nitrogen metabolism has been shown to be important in the regulation of sporulation and solventogenesis, and the enzyme glutamine synthetase, encoded by the gene ginA, is central to this aspect of metabolism. This work represents a continuation of studies on the glutamine synthetase enzyme of C. acetobutylicum NCP 262. Previous work identified a gene, glnR, which is thought to encode an anti terminator protein involved in the regulation of ginA transcription. An attempt was made to demonstrate a regulatory role for glnR in a system using the cloned C. acetobutylicum NCP 262 ginA with and without glnR in the E. coli glnAntrBC mutant YMCll. Although the enzyme was efficiently expressed and fully functional, no evidence could be found of any influence of glnR on GS activity in the heterologous host. In an attempt to locate other genes involved in ginA regulation the region upstream of ginA in C. acetobutylicum NCP 262 was sequenced. Although no aceesory regulatory genes were found, an incomplete open reading frame encoding a putative aspartokinase or bifunctional aspartokinase/homoserine dehydrogenase was identified. As attempts to reconstitute the C. acetobutylicum NCP 262 ginA regulatory system in E. coli were unsuccessful, it was necessary to find an alternative to heterologous host. C. beijerinckii NCIMB 8052, which is closely related to C. acetobutylicum NCP 262, was evaluated as a model organism for the study of nitrogen metabolism in the latter. It was found that organic nitrogen in the form of cas amino acids was preferred over ammonium, and that GS activity was induced under conditions of nitrogen limitation, and repressed in cultures grOWL in the presence of high concentration of cas amino acids. Southern hybridisation experiments identified homologues of ginA, glnR and gltA in C. beijerinckii NCIMB 8052, and a clone was isolated from a partial gene library of this organism which complemented glutamine auxotrophy in E. coli YMCll. The clone was sequenced and found to carry two complete and one incomplete ORF's which shared a high degree of nucleotide sequence similarity with ginA, ginR and gltA genes of C. acetobutylicum NCP 262 (87.8%, 86.5.% and 86.8% respectively). In addition, the relative arrangement of the genes was similar. Primer extension experiments identified four transcriptional start sites, two of which corresponded approximately to those previously identified in C. acetobutylicum NCP 262. Transcription from all four was found to increase under conditions of nitrogen limitation. Leaders of three of the transcripts were found to be capable of forming identical terminator structures upstream of the start codon of ginA, however potential antiterminator structures differed for each transcript. A reporter system was developed for use in C. beijerinckii NCIMB 8052, based on the eglA gene cloned from C. acetobutylicum NCP 262, cloned into the Bacillus/Clostridium shuttle vector pFNKl. When eglA was under the control of its own promoter, the endoglucanase activity was expressed and efficiently secreted into the culture medium by C. beijerinckii NCIMB 8052. The pH and temperature optima of the enzyme activity were found to be between 5.0 and 6.0 and 45°C respectively. These parameters differed from those previously reported for an endoglucanase activity in C. acetobutylicum NCP 262. Expression of eglA appeared to be repressed by cellobiose and fructose, but not by glucose, sucrose or galactose. A promoterless eglA was placed under the control of ginA and scr promoters. Very little eglA expression was observed for the scr promoter-eglA in any of the above-mentioned carbon sources, indicating either a disruption of normal regulation in the cell, or the absence of essential regions on the cloned promoter fragment. The ginA promotereglA fusion produced large amounts of endoglucanase activity under conditions of nitrogen excess and limitation, indicating the absence of a negative regulatory factor. GS activity in the same cultures was regulated normally, indicating that the loss of regulation was most likely to be due to the absence of an essential factor on the fusion construct. It was shown, nevertheless, that efficient expression of the reporter could be obtained under the control of a heterologous promoter. Potential problems with the reporter system were discussed and suggestions were made for improvement ofthe system. v Transcription from all four was found to increase under conditions of nitrogen limitation. Leaders of three of the transcripts were found to be capable of forming identical terminator structures upstream of the start codon of ginA, however potential antiterminator structures differed for each transcript. A reporter system was developed for use in C. beijerinckii NCIMB 8052, based on the eglA gene cloned from C. acetobutylicum NCP 262, cloned into the Bacillus/Clostridium shuttle vector pFNKl. When eglA was under the control of its own promoter, the endoglucanase activity was expressed and efficiently secreted into the culture medium by C. beijerinckii NCIMB 8052. The pH and temperature optima of the enzyme activity were found to be between 5.0 and 6.0 and 45°C respectively. These parameters differed from those previously reported for an endoglucanase activity in C. acetobutylicum NCP 262. Expression of eglA appeared to be repressed by cellobiose and fructose, but not by glucose, sucrose or galactose. A promoterless eglA was placed under the control of ginA and scr promoters. Very little eglA expression was observed for the scr promoter-eglA in any of the above-mentioned carbon sources, indicating either a disruption of normal regulation in the cell, or the absence of essential regions on the cloned promoter fragment. The glnA promotereglA fusion produced large amounts of endoglucanase activity under conditions of nitrogen excess and limitation, indicating the absence of a negative regulatory factor. GS activity in the same cultures was regulated normally, indicating that the loss of regulation was most likely to be due to the absence of an essential factor on the fusion construct. It was shown, nevertheless, that efficient expression of the reporter could be obtained under the control of a heterologous promoter. Potential problems with the reporter system were discussed and suggestions were made for improvement of the system.